IMPLEMENTASI KURIKULUM MERDEKA DIPONDOK PESANTREN ISLAMIYAH GUNUNG RAYA PADANGLAWAS UTARA - Robiatul Adawiyah Siregar; Satrio Abdillah (Yayasan Baitul Hikmah al-Zain, 2024)
The development of education in Indonesia continues to experience better progress. Various innovations have been developed aimed at improving the quality of education at various levels of education. One of the innovations put forward is an independent curriculum. This independent curriculum is also implemented at the Gunung Raya Islamiyah Islamic Boarding School, North Padanglawas Regency. Therefore, this research aims to determine the implementation of the independent curriculum at the Gunung Raya Islamiyah Islamic Boarding School, North Padanglawas Regency. The research was conducted using qualitative research. The research results found that the independent learning curriculum implemented included USBN and National Examination which were replaced with assessments and Arabic language immersion. Astrology, Mathematics and Natural Sciences group, Social Sciences group and tablig week routine activities